Comparison of impact of synchronization protocols applied to ewes on pregnancy rate in Turkey with bayesian meta-analysis - MAT, Burak; POLAT, Murat; ÖZEL, Zeynep; DEMİRSÖZ, Mert (Journal of Advances in VetBio Science and Techniques, 2021)
The present study carried a meta-analysis of the pregnancy rates of different synchronization protocols implemented in ewes in Turkey. A common pregnancy rate was estimated by coalescing pregnancy rates, and the heterogeneity between the studies was explored. All studies were carried out independently. This article compiled 28 studies that determined the pregnancy rate for 2,437 ewes in the synchronization studies between the years 1995–2020. The overall effect size of the meta-analysis was found to be 0.66 (95% confidence interval; 0.58–0.74) (p
Keywords: Veteriner Bilimleri; ewes; meta-analysis; pregnancy rate; synchronization; Turkey; Veterinary Sciences